The DiabCare Asia 2008 study – Outcomes on control and complications of type 2 diabetic patients in Indonesia (Medical Journal of Indonesia, 2010)
Aim: To collect information on diabetes management, diabetes complications, and awareness of self-control in diabetic population of the country. This study also evaluated the physician perspectives, psychological aspects, and quality of life of diabetic patients. Methods: This was a non-interventional, cross-sectional study, which recruited 1832 patients from secondary and tertiary medical centers across Indonesia. Data on demography, medical history, risk factors and clinical examination reports including laboratory assessments were collected from medical records of patients. Blood samples of all patients were collected for centralized HbA1c measurements. Results: Among 1832 patients, 1785 individuals were eligible for analysis. The mean age of the patients was 58.9+9.6 years. The mean duration of diabetes was 8.5+7.0 years. Majority (97.5%) of the patients had type 2 diabetes. 67.9% had poor control of diabetes (A1c:8.1 ± 2.0%). 47.2% had FPG>130 mg/dL (161.6 ±14.6 mg/dL). Dyslipidemia was reported in 60% (834/1390) and 74% (617/834) of those received lipid lowering treatment. Neuropathy was most common complication (63.5%); other complications were: Diabetic retinopathy 42%, nephropathy 7.3%, severe late complications 16.9%, macrovascular complications 16%, microvascular complications 27.6%. About 81.3% of patients were on OADs (± insulin), 37.7% were on insulin (±OADs). Majority used biguanides followed by sulfonylureas. Human insulin was used by 73.2%, premix regimen 58.5%, analogues usage was 24.9%. Majority of the WHO-5 well being index responses fell in positive territory Conclusion: Poor glycaemic control in majority of patients is a concern. There is a need for a large proportion of patients to be adjusted to more intensive pharmacotherapy and a multi-disciplinary approach for management should be adopted. The study fi ndings should be communicated to policymakers and physicians to help them provide proper healthcare and its facilities in Indonesia. (Med J Indones 2010; 19:235-44) Keywords: DiabCare, DiabCare Indonesia, Diabetes complications, Dyslipidaemia, Glycaemic control, Hypertension.